Penyelesaian Tindak Pidana Penganiayaan Melalui Pendekatan Restorative Justice Ditinjau Dari Perspektif Hukum Pidana Islam - Rizky Al Ikhsan; Dahyul Daipon (Universitas Ekasakti, 2024)
In discussing Islamic Law in the midst of National Law, the focus will be on the position of Islamic Law in the National Law system. The Indonesian legal system, as a result of its historical development, is plural. It is called that because until now in the Republic of Indonesia several legal systems have been implemented which have their own style and structure. In fact, Islamic law has become the living law in Indonesian society since the arrival of Islam to the archipelago. Many legal cases, especially those referred to in the Criminal Code as negligence that causes the loss of another person's life, can be resolved amicably by compensating for losses. Resolving the crime of taking another person's life by means of peace is similar to the qishas-diyat provisions in Islamic criminal law. The Problem Formulation (1) How is restorative justice implemented in resolving cases of the crime of illtreatment based on the Republic of Indonesia Attorney General's Regulation Number 15 of 2020? and (2) How to resolve criminal acts through a restorative justice approach to criminal acts of abuse from the perspective of Islamic Criminal Law. The conclusions of this research are: (1) The Prosecutor's Office as the agency that holds control over prosecution or Dominus Litis has a very important role in upholding justice in society, especially in implementing Restorative Justice. Restorative Justice is considered as a renewal of justice enforcement that is oriented towards restoring or restoring a person's condition as a victim of a crime. To ensure legal certainty in the implementation of Restorative Justice, Prosecutor's Regulation Number 1 of 2020 concerning Termination of Prosecution Based on Restorative Justice was issued. With this Perja, giving prosecutors the authority to stop prosecutions based on restorative justice is a breakthrough in resolving criminal acts. Since the publication of Prosecutor's Regulation Number 15 of 2020, the number of cases successfully resolved using the Restorative Justice approach is 4,443 cases. In detail, in 2020, 192 cases were approved using Restorative Justice and 44 were rejected. (2) The restorative justice approach provides attention and protection to victims or their families. Perpetrators of criminal acts can be held responsible for their actions and compensate for losses and future relationships can be restored. This also has similarities with the qishas-diyat provisions in Islamic Criminal Law. Criminal qishas (equivalent) and diyat (compensation) are the rights of the victim or their heirs, so that they can provide amnesty (forgiveness) to the perpetrator. If you forgive, then the crime of qishas will be extinguished, replaced with diyat (compensation), even without diyat at all.